The heat-pump market in Italy: an in-depth economic study about the reasons for a still unexpressed potential. Issue 2 (19th March 2019) - Pieve, Maurizio; Trinchieri, Raniero
Abstract: In this paper, the Italian heat-pump (HP) market is presented, with an overview over the past 10 years. In order to highlight market potential and barriers, a comparison is proposed between the economic performances of two different heating and domestic hot-water systems, air-to-water HPs and condensing boilers, based on several factors, such as energy costs, thermal loads, climatic conditions, HP-performance classes and some economic indicators such as the payback time and the interest rate. The results are presented in a parametric form, which may be profitably used for a comparative analysis with other European countries. The first part of the paper deals with the analysis of the current Italian HP market, to show its still unexpressed potential. The second part analyses the HP economic convenience with respect to the most commonly used heating technology, i.e. the gas boiler, under conditions typical of the Italian climate. The comparison is carried out in terms of two economic indicators: additional acceptable cost and net present value. The main results show that HP technology is economically competitive in most Italian climatic zones, with a strong dependence on the HP-performance class. In particular, if the best-performing class was adopted, economic gains would be guaranteed over the gas boiler, even with significant variations in the main influencing variables. Thus, the economic issue does not seem to be a limiting factor for HP technology diffusion, at least if the current incentives are maintained. Rather, some other barriers should be removed, such as the supply chain, the training of installation personnel and the final-user awareness.